2016
DOI: 10.1038/srep37895
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR-Cas9 Assisted Non-Homologous End-Joining Strategy for One-step Engineering of Bacterial Genome

Abstract: Homologous recombination-mediated genome engineering has been broadly applied in prokaryotes with high efficiency and accuracy. However, this method is limited in realizing larger-scale genome editing with numerous genes or large DNA fragments because of the relatively complicated procedure for DNA editing template construction. Here, we describe a CRISPR-Cas9 assisted non-homologous end-joining (CA-NHEJ) strategy for the rapid and efficient inactivation of bacterial gene (s) in a homologous recombination-inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 51 publications
5
107
0
Order By: Relevance
“…Su et al attempted to co‐express Ku and LigD from M. tuberculosis along with a typical SpCas9 targeting machine in E. coli , in order to achieve genome editing without introducing a repair template. The study showed that MtKu and MtLigD efficiently rescued the bacteria from fatal genome targeting, which created deletions surrounding the target site ranging from ten to hundreds of base pairs . Moreover, by simultaneously using a pair of sgRNA at distant locations, large genomic fragment deletions up to 17 kB are manageable, which is promising in manipulating large gene cluster deletion in bacteria.…”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 97%
See 2 more Smart Citations
“…Su et al attempted to co‐express Ku and LigD from M. tuberculosis along with a typical SpCas9 targeting machine in E. coli , in order to achieve genome editing without introducing a repair template. The study showed that MtKu and MtLigD efficiently rescued the bacteria from fatal genome targeting, which created deletions surrounding the target site ranging from ten to hundreds of base pairs . Moreover, by simultaneously using a pair of sgRNA at distant locations, large genomic fragment deletions up to 17 kB are manageable, which is promising in manipulating large gene cluster deletion in bacteria.…”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 97%
“…To exploit the usage of NHEJ, it is a good idea to reconstitute exogenous Ku and LigD into the bacteria without intrinsic NHEJ machines. Su et al attempted to co‐express Ku and LigD from M. tuberculosis along with a typical SpCas9 targeting machine in E. coli , in order to achieve genome editing without introducing a repair template. The study showed that MtKu and MtLigD efficiently rescued the bacteria from fatal genome targeting, which created deletions surrounding the target site ranging from ten to hundreds of base pairs .…”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2015) stated a 14% efficiency for the insertion of an 8 kb fragment while others achieved a 50% efficiency for the insertion of a 10 kb construct (Bassalo et al, 2016). Operon deletions of 10 kb were reported with an efficiency of 25% (Su et al, 2016). All reported efficiencies dropped significantly when fragment size was increased and varied greatly between the different methods.…”
mentioning
confidence: 99%
“…Non-recombined cells will die as a consequence of the double-stranded break. Operon deletions of 10 kb were reported with an efficiency of 25% (Su et al, 2016). However, these methods apply homologous recombination for DNA repair and hence suffer from the same size limitations for introducing DNA fragments as stated above.…”
mentioning
confidence: 99%